Influence of leptin administration to pregnant female mice on obesity development, taste preferences, and gene expression in the liver and muscles of their male and female offspring - E. I. Denisova; M. M. Savinkova; E. N. Makarova (Вавиловский журнал генетики и селекции, 2021)
The consumption of food rich in sugar and fat provokes obesity. Prenatal conditions have an impact on taste preferences and metabolism in the adult offspring, and this impact may manifest differently in different sexes. An increase in blood leptin level in pregnant females reduces the risk of obesity and insulin resistance in the offspring, although the mechanisms mediating this effect are unknown. Neither is it known whether maternal leptin affects taste preferences. In this study, we investigated the effect of leptin administration to pregnant mice on the development of diet-induced obesity, food choice, and gene expression in the liver and muscles of the offspring with regard to sex. Leptin was administered to female mice on days 11, 12, and 13 of pregnancy. In male and female offspring, growth rate and intake of standard chow after weaning, obesity development, gene expression in the liver and muscles, and food choice when kept on a high-calorie diet (standard chow, lard, sweet cookies) were recorded. Leptin administration to pregnant females reduced body weight in the female offspring fed on the standard diet. When the offspring were given a high-calorie diet, leptin administration inhibited obesity development and reduced the consumption of cookies only in males. It also increased the consumption of standard chow and the mRNA levels of genes for the insulin receptor and glucose transporter type 4 in the muscles of both male and female offspring. The results demonstrate that an increase in blood leptin levels in pregnant females has a sex-specific effect on the metabolism of the offspring increasing resistance to obesity only in male offspring. The mechanism underlying this effect includes a shift in food preference in favor of a balanced diet and maintenance of insulin sensitivity in muscle tissues.